Atenolol pharmacokinetics in patients on continuous ambulatory peritoneal dialysis. - Salahudeen, A K (1984)
The elimination of atenolol (20 mg i.v.) has been studied in seven patients with renal failure on continuous ambulatory peritoneal dialysis (CAPD). Although atenolol was eliminated in the peritoneal fluid, the amount recovered in 24 h was relatively low (1.2 +/- 0.15 mg). The calculated urinary (n = 4) and peritoneal (n = 7) clearance was 0.289 +/- 0.058 l/h and 0.152 +/- 0.018 l/h respectively. This was considerably less than calculated total body clearance (1.21 +/- 0.086 l/h). The kinetics of atenolol in CAPD are worthy of further study.